2016
DOI: 10.1103/physrevd.93.023511
|View full text |Cite
|
Sign up to set email alerts
|

Late-time evolution of cosmological models with fluids obeying a Shan-Chen-like equation of state

Abstract: Classical as well as quantum features of the late-time evolution of cosmological models with fluids obeying a Shan-Chen-like equation of state are studied. The latter is of the type p = w eff (ρ) ρ, and has been used in previous works to describe, e.g., a possible scenario for the growth of the dark-energy content of the present Universe. At the classical level the fluid dynamics in a spatially flat FriedmannRobertson-Walker background implies the existence of two possible equilibrium solutions depending on th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In [12], it was shown that these difficulties can be overcome by means of another Born-Infeld type field -the quasitachyon, which will be briefly mentioned in the next section. Some global aspects of quantum cosmology similar to the ones here were recently investigated in [13,16,[24][25][26][27][28]. These concern, in particular, the fate of classical singularities.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In [12], it was shown that these difficulties can be overcome by means of another Born-Infeld type field -the quasitachyon, which will be briefly mentioned in the next section. Some global aspects of quantum cosmology similar to the ones here were recently investigated in [13,16,[24][25][26][27][28]. These concern, in particular, the fate of classical singularities.…”
Section: Introductionmentioning
confidence: 64%
“…The solutions in the region T > 0, s < 2 3β− are attracted to the particular solution with s = 2 3β+ , cf. (28). All other solutions end in a Big Brake.…”
Section: Tachyonic and Other Born-infeld Type Fields In Classical Cos...mentioning
confidence: 99%
“…Also, we will check whether our claim that the non-ideality of the fluid does not affect the values of the cosmological parameters at equilibrium, but for the age of the Universe, should be re-examined. Our results about the classification of the singularities depending on certain relationships between the parameters of the model are also important in light of the studies of their quantum corrections (accounted for by the Wheeler-de Wit equation), as done for example in the case of dark energy models based on the non-ideal Shan-Chen fluid in which the cases of singularities characterized by a finite or diverging energy density where compared and contrasted [75]. and in general they depend on the values of the free parameters α 1 ,...,α n .…”
Section: Discussionmentioning
confidence: 88%
“…Our cosmological models are not affected by a Type IV singularity. Our analysis was completely classical and whether quantum gravity corrections á la Wheeler-DeWitt affect this picture will be clarified in a future project, as for example done in [145]. Other interesting future projects may consist in analyzing the astrophysical data about recombination epoch, 21-cm line excess at cosmic dawn, and Lyman α forest by exploiting the existence of a radiation-dominated epoch in our models; this can tame the previously mentioned disagreement between the thermodynamical Le Chatelier-Braun principle and the fact that a dark matter epoch should have come before the dark energy one [67,68] since those phenomena are usually addressed via interacting scenarios [146][147][148].…”
Section: Discussionmentioning
confidence: 99%